Efficacy and safety of cinobufacini injection combined with vinorelbine and cisplatin regimen chemotherapy for stage III/IV non-small cell lung cancer: A protocol for systematic review and meta-analysis of randomized controlled trials. Issue 31 (31st July 2020) - Li, Qian; Liang, Ren-Long; Yu, Qian-Ru; Tian, De-Qing; Zhao, Li-Na; Wang, Wen-Wen; Xiao, Hua; Yong, Xiao-Jia; Peng, Xiao-Dong
Abstract: Background: The main component of cinobufacini injection is dry toad skin, which is used as adjuvant therapy for stage III/IV non-small cell lung cancer patients in long-term combination with vinorelbine and cisplatin. However, the efficacy and safety of this combination therapy remain unclear. Methods: A systematic review and meta-analysis will be conducted following the preferred reported items for systematic review and meta-analysis guidelines. Two independent reviewers (LRL and ZLN) will carry out a comprehensive search of the PubMed, Web of Science, Cochrane Library, EMBASE, the Chinese Science and Technology Periodical Database, China National Knowledge Infrastructure, Wanfang Databases, China Biology Medicine. The last search date will be July 30, 2020. Reference list of all selected articles will independently screened to identify additional studies left out in the initial search. The Cochrane Risk of Bias Tool will be used to evaluate the risk of bias of the randomized controlled trials. Outcome index: The main efficacy indicators were based on the objective efficacy evaluation criteria of the World Health Organization antineoplastic drugs or the objective efficacy evaluation criteria of solid tumors established by RECIST. Secondary criteria Karnofsky performance scale (KPS) score, pain efficacy criteria, side effects of chemotherapy such as myelosuppression and gastrointestinal symptoms. Assessment of risk of bias and data synthesis will be conducted using Review Manager V5.3 software. Results: This study will systematically evaluate the efficacy and safety of cinobufacini combined with vinorelbine and cisplatin in the treatment of stage III/IV non-small cell lung cancer. The results of this systematic review will be published in peer-reviewed scientific journals. Ethics: The ethical approval is not required since systematic review is based on published studies. INPLASY registration number: INPLASY202060091. Abstract : Supplemental Digital Content is available in the text